INTERNALISASI NILAI NASIONALISME DALAM PEMBELAJARAN PKn PADA SISWA MAN 2 MODEL BANJARMASIN - Mitha, Mitha (Lambung Mangkurat University Indonesia, 2014)
Internalization of nationalism value is an effort of developing learning strategy which includes nationalism values in building studentsâ moral in MAN 2 Model Banjarmasin. This effort is done to develop the civic education learning as lesson material which is integrated with nationalism value in order to increase the studentsâ learning outcome and change the studentsâ attitude in learning in high school so that the self-awareness on nationalism can appear. Furthermore, this research aims to find out the program and the internalization strategy of nationalism value which are done by the civic education teachers to the students and the implementation of nationalism value done by the students of MAN 2 Model Banjarmasin.This method used in this research is qualitative method. The technique of collecting data is by using observation to observe directly the internalization process of nationalism value by the teachers, interview to get the information needed directly from the informants as the data source, and documentation to ease the researcher in collecting the data, both written document and pictures as the data source.The finding of this research indicates thatthe program and the internalization strategy of nationalism value by the civic education teachers have been run well which apply various methods and strategies. However, the implementation which is done by the students is still low because of the environment factor.Based on the finding of this research, it is suggested that the teachers should increase the effort to instill the nationalism value to the students by using various, effective, and interesting ways and methods in order to keep boosting the degree of studentsâ nationalism. It is also suggested the school should create school culture which has character to make the students not only smart academically, but also have moral, good behaviour and high nationalism spirit.Â Keywords: internalization of value, nationalism, civic education learning